Environmental impact of municipal wastewater management based on analysis of life cycle assessment in Denpasar City - Suryawan, I.W.K. (Desalination Publications, 2021)
The municipal wastewater treatment in Denpasar City has a service target of 100, which supports the Ministry of Public Works and Public Housing (PUPR), Indonesia. The total wastewater produced by Denpasar City is around 43,920 m3/y. Currently, a centralized wastewater treatment plant treats only 3 of wastewater. In comparison, the rest of 96.8 is carried out by onsite treatment with septic tanks, and 0.2 is directly discharged into the environment (open defecation). This study examined the eutrophication impact generated by each wastewater management based on the analysis of the Life Cycle Assessment (LCA). The analysis was conducted using the Simapro ver. 9.1 software and observed the eutrophication impact potential generated for each wastewa-ter management system. The inventory results showed that open defecation management was the largest pollution load, although the quantity of water contributed was very low (0.2). The weighting of the impact of eutrophication, global warming potential, photochemical oxidation, and water scarcity on fecal management showed the same weight for open defecation behavior (346.8 pt). In comparison, the wastewater treatment plant (WWTP) and septic tanks were 2.1 and 52.1 pt, respectively. Open defecation behavior must be eliminated by formulating a right strategy. Treatment with septic tanks should be directed to centralized treatment by applying the tertiary treatment. Also, a sustainable development strategy needs to be applied in Denpasar City and more broadly throughout Indonesia and other developing countries where the population still applies open defecation. Â© 2021 Desalination Publications. All rights reserved.